2019
DOI: 10.1371/journal.pone.0218189
|View full text |Cite|
|
Sign up to set email alerts
|

Chemogenomic profiling in yeast reveals antifungal mode-of-action of polyene macrolactam auroramycin

Abstract: In this study, we report antifungal activity of auroramycin against Candida albicans , Candida tropicalis , and Cryptococcus neoformans . Auroramycin, a potent antimicrobial doubly glycosylated 24-membered polyene macrolactam, was previously isolated and characterized, following CRISPR-Cas9 mediated activation of a silent polyketide synthase biosynthetic gene cluster in Streptomyces rosesporous NRRL 15998. Chemogenomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The mode of action of the compounds may be through mycelial growth inhibition. However, other studies suggested that the compounds may act through cell membrane damage, compromising the integrity and permeability of fungal cells (Haraguchi et al., 1999; Leite et al., 2014) and possible leakage of cations from the cytoplasm (Wong et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The mode of action of the compounds may be through mycelial growth inhibition. However, other studies suggested that the compounds may act through cell membrane damage, compromising the integrity and permeability of fungal cells (Haraguchi et al., 1999; Leite et al., 2014) and possible leakage of cations from the cytoplasm (Wong et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, to our surprise, the production rates in R5 media were comparable between the CH and the latter S. coelicolor M1152 strain. To push the boundaries further, we selected the cryptic auroramycin BGC, spanning approximately 106 kb, from S. roseosporus NRRL 15 998 [46,58]. Using our recently described CAP-TURE method [22] and from our in-house strain library, we cloned and expressed this BGC heterologously.…”
Section: Discussionmentioning
confidence: 99%
“…Auroramycin (37) was a rare member of polyene macrolactams with antifungal bioactivity. The action of auroramycin in yeast cells was that it disrupted the structural organization of the vacuolar and the integrity of membranes, which differed from amphotericin B. Auroramycin was able to cause ionic stress and hyperpolarization of the yeast plasma membrane, which resulted in the microcosmic phenomenon of cation leakage from the cytoplasm [134].…”
Section: Mechanism Of Actionmentioning
confidence: 99%